3D evaluation of maxillary morphology in Marfan growing subjects: a controlled clinical study - Giuseppina Laganà; Daniel Palmacci; Giovanni Ruvolo; Paola Cozza; Valeria Paoloni (SpringerOpen, 2019)
Abstract Background Marfan syndrome is a rare autosomal dominant inherited disease of the connective tissue associated with various craniofacial abnormalities. Aim of the present study was to assess the variability of palatal shape in a sample of 31 Marfan patients compared to a control group of no syndromic subjects, in two stages of dentition, by using 3D geometric morphometric analysis. Methods Thirty one growing subjects with Marfan syndrome were selected and divided into two subgroups: MG1 with mixed dentition (10 M, 6F, mean age 7+/− 0.7 years), MG2 with permanent dentition (8 M, 7F, mean age 13+/− 0,5 years). Each subgroup was compared to a control group (CG1 mixed dentition, 9 M, 7F, mean age 7.6+/− 0.5 years; CG2 permanent dentition, 9 M, 6F, mean age 12.8+/− 0.7 years) matched on age, sex distribution, stage of dentition and skeletal maturation. Then the two subgroups were compared one to each other. For each patient maxillary dental casts were taken, scanned and digitized. 3D geometric morphometric methods were applied. Procrustes analysis was used and principal component analysis was performed to reveal the main patterns of palatal shape variation. Results Both Marfan subgroups showed important reductions in the transversal plane associated with a deep palatal vault when compared to the control groups (MG1 vs CG1 P = 0,003; MG2 vs CG2 P = 0,07). Moreover a statistically significant difference between the palatal shape of MG1 and MG2 was found (P = 0.017) showing a significant worsening of palatal depth and constriction from mixed to permanent dentition in Marfan subjects. Conclusion Marfan subjects showed a specific palatal morphology with maxillary constriction and deeper palatal vault when compared to a control group of healthy subjects. The constriction and the depth of the palatal vault in Marfan patients worsen from mixed dentition to permanent dentition more then in no syndromic subjects.